Endoscopic extra-cavitary drainage of pancreatic necrosis with fully covered self-expanding metal stents (fcSEMS) and staged lavage with a high-flow water jet system - Smith, Ioana B.; Gutierrez, Juan P.; Ramesh, Jayapal; Wilcox, C. Mel; Mönkemüller, Klaus E. (Endoscopy International Open, 2015)
Aim: To present a novel, less-invasive method of endoscopic drainage (ED) for walled-off pancreatic necrosis (WON).We describe the feasibility, success rate, and complications of combined ED extra-cavitary lavage and debridement of WON using a biliary catheter and high-flow water jet system (water pump).Patients and methods: Endoscopic ultrasound (EUS)-guided drainage was performed with insertion of two 7-Fr, 4-cm double pigtail stents. Subsequently a fully covered self-expanding metal stent (fcSEMS) was placed. The key aspect of the debridement was the insertion of a 5-Fr biliary catheter through or along the fcSEMS into the cavity, with ensuing saline lavage using a high-flow water jet system. The patients were then brought back for repeated, planned endoscopic lavages of the WON. No endoscopic intra-cavitary exploration was performed.Results: A total of 17 patients (15 men, 2 women; mean age 52.6, range 24 – 69; mean American Society of Anesthesiologists [ASA] score of 3) underwent ED of WON with this new method. The mean initial WON diameter was 9.5 cm, range 8 to 26 cm. The total number of ED was 84, range 2 to 13. The mean stenting period was 42.5 days. The mean follow-up was 51 days, range 3 to 370. A resolution of the WON was achieved in 14 patients (82.3 %). There were no major complications associated with this method.Conclusion: ED of complex WON with fcSEMS followed by repeated endoscopic extra-cavitary lavage and debridement using a biliary catheter and high-flow water jet system is a minimally invasive, feasible method with high technical and clinical success and minimal complications.